Фінансовий аналіз банківського сектора в Польщі - Гальбарчик, T. (Видавництво Львівської політехніки, 2014)
Наведено специфіку та спектр фінансового аналізу банків як фактор впливу на їх імідж та стабільність, а таким чином – і на стабільність всього фінансового сектора. Проаналізовано вибрані сфери діяльності банківського сектора Польщі в 2010–2013 рр. In the market economy, banks act as financial intermediary. On one hand, they want to make profit, but on the other hand they are called public-trust institutions. Since profit maximization is not possible without taking risks, that is why risk taking must be controlled. The activity of banks is therefore supervised by the Commission for Financial Supervision, the National Polish Bank or Bank Guarantee Fund. Other participants in the economic process must also have a clear picture of their financial position and management results. In the context of increasing competition and increasing the risk of making decisions by banks, an access to objective assessments of the economic – financial situation of banks is of particular importance. The assessments should be based on the analysis of the data presented in the financial statements. Since the credibility of carried out evaluations is determined by the credibility and reliability of data on which they were made, the bank financial statements are subject of examination, the purpose of which is to express an opinion by the auditor, whether it is consistent with the applicable accounting rules (policy) and whether it fairly and clearly shows the asset and financial situation, as well as the bank profit. Financial analysis can reduce the risk and eliminate the consequences of bad decisions, makes it possible to take appropriate action in order to improve efficiency, better utilization of resources, to meet the expectations of the owners and to ensure an appropriate level of liquidity and capital adequacy. Apart from the bank managers, others use it as well. The main objective of such tools is to assist the processes of decision-making at various levels. Furthermore, financial analysis has an impact on shaping the image of the bank and the evaluation of its credibility. Presentation of the characteristics and scope of the banks financial analysis, as a factor affecting their image and their stability, is therefore the aim of the author’s article. This is of particular importance due to the fact that at the end of 2013 the value of the assets of the financial system in Poland (without NBP) was nearly 2.3 billion zł, of which 62.2% was in the banking sector. Moreover, taking into account the relations between banks and other entities of the financial market, it can be concluded that the stability of the banking sector is crucial for the stability of the entire financial system in Poland. The scope of the financial analysis is related to the macro scale and covers the entire banking sector, i.e. commercial banks (state-owned and joint-stock companies), credit units and credit institutions. The paper presents the structure of the sector (including the participation of foreign capital and the directions of its origin) and its place in the Polish financial system taking into account the amount of assets. The subject matter of the scope includes preliminary financial statements analysis (the analysis of dynamics and structure of the balance sheet and profit and loss account - without the report of funds flow and the statement of changes in equity - and capital adequacy) and ratio analysis on the basis of data from financial statements. The ratio analysis was limited to the assessment of the most important spheres of bank activities, i.e. solvency ratios, liquidity measures and efficiency. The source of the pooled data for the banking sector have been reports published by the FSA. The time period of the analysis covers the years 2010–2013, and the spatial range takes into account system solutions in assessing the solvency and liquidity of banks and the already mentioned above, position in the Polish financial system. Due to limitations in the volume of the article, the analysis of the competition from other institutions has been omitted. The analysis leads to the following conclusions: number of entities conducting banking activities remains stable, while there was a slight increase of the contribution of banks controlled by domestic investors; the banking sector in Poland is characterized by maintaining strong capital position. Throughout the period there was a growing surplus of own funds in relation to the entire capital requirement, which means that the amount of own funds was appropriate to the scale of the risk involved; the balance sheet structure confirms the dominant contribution of traditional banking operations (deposit and credit activities) in shaping the balance sheet total. The effect of this is also the predominant contribution of income interests in shaping banking activity profit and – indirectly – banks profit; the banks compliance requirements for solvency and liquidity should be assessed positively. Both capital adequacy ratios (CAR and Tier 1) and shorter-term liquidity measures were maintained at the required level; despite difficult external conditions, the net profit achieved by the banking sector in 2012-2013, fell only slightly, the consequence of which was, however, worsening of the main measures of effectiveness; the analysis confirmed the key role of banks for the stability of the financial system in Poland. At present and in the near future, the stability of the banking sector does not seem to be threatened.
Financial analysis of the banking sector in Poland
Keywords: банківський сектор; банківські установи Польщі; діяльність; стабільність; імідж; фінансовий аналіз; методи; підходи; banking; banks Poland; activity; stability; image; financial analysis; methods; approaches